Consumable Analytics. Issue 4 (May 2017) - Chartier, Tim
Abstract : Basketball entails running up and down the court. I remember practice in middle school where we'd run up and touch the baseline and then back to touch the other baseline. We'd run up and back again and again. We could have easily tracked, as possibly my coach did, how far we'd run. We'd also practice changing direction on the coach's whistle. Some players could alter direction quickly, while others seemed more concerned about staying on their feet than the rate of their acceleration. Some players could run and run. Others could dart from spot to spot. Game strategies were often designed to monopolize on such skills. How well did we actualize those strategies? Remember, it was middle school basketball, so we also had many other fundamental objectives—like consistently scoring on open shots.